1981
DOI: 10.1017/s0025315400023018
|View full text |Cite
|
Sign up to set email alerts
|

Startle Response in Herring: The Effect of Sound Stimulus Frequency, Size of Fish and Selective Interference With The Acoustico-Lateralis System

Abstract: Herring (Clupea harengus L.) show a characteristic 'startle' response when subjected to vibrational stimuli from a diaphragm in the wall of their tank. Threshold measurements on fish from 2-8 to 17 cm total length tested at frequencies from 70 to 200 Hz showed that the response was elicited by sound pressures between 2 and 18 Pa, the most sensitive fish being in the length range from 8-11 cm. Intermediate-sized fish of 12-13 cm also responded to sounds from a loudspeaker in air above the tank, the mean thresho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0

Year Published

1988
1988
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 10 publications
3
35
0
Order By: Relevance
“…A given sound pressure should move the bulla the same amount, regardless of fish size. If this is the mechanism of higher frequency sound detection in shad, as has been shown for other Clupeiformes (Blaxter and Hoss, 1981), then one should expect no change in auditory sensitivity with shad development once the bullae are filled, as was shown by our ABR results. Bulla inflation was complete by 14·mm, much before the size at which animals responded to ultrasound (26·mm).…”
Section: M Higgs and Otherssupporting
confidence: 69%
See 1 more Smart Citation
“…A given sound pressure should move the bulla the same amount, regardless of fish size. If this is the mechanism of higher frequency sound detection in shad, as has been shown for other Clupeiformes (Blaxter and Hoss, 1981), then one should expect no change in auditory sensitivity with shad development once the bullae are filled, as was shown by our ABR results. Bulla inflation was complete by 14·mm, much before the size at which animals responded to ultrasound (26·mm).…”
Section: M Higgs and Otherssupporting
confidence: 69%
“…The indirect pathway allows the ear to respond to higher frequencies than would be possible without this pathway (Blaxter and Hoss, 1981).…”
mentioning
confidence: 99%
“…Casagrand et al (1999) also recalculated the sound pressure threshold given by Lewis and Rogers (1998), for eliciting directional startle behaviours in goldfish, to an acceleration threshold of 0.03·m·s -2 . and Blaxter and Hoss (1981) found the threshold for acoustic startle in the herring to be approximately 70·dB above the absolute threshold, corresponding to pressures in the range [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and to accelerations within the range 0.01-0.04·m·s -2 . The latency of acoustic or vibratory startle responses in fish are typically in the range 5-40·ms depending on the stimulus intensity and frequency (Eaton et al, 1977;.…”
Section: Startle Thresholdsmentioning
confidence: 93%
“…In natural conditions, neither pressure nor acceleration will appear separately, and it is thus not surprising that both components are necessary to elicit startle in fish. Even though acceleration conveys the crucial directional information to the fish, several studies have shown that the startle escape appears to be triggered only when the pressure reaches a critical value (Blaxter and Hoss, 1981;Blaxter and Fuiman, 1990;Canfield and Eaton, 1990). and Guzik et al (1999) have adopted the original phase model for directional hearing to explain the directional startle responses.…”
Section: Directionality Of the Startle Responsesmentioning
confidence: 99%
“…2H). Blaxter and Hoss (1981) exposed herring to 0.07-0.2 kHz signals, found startle responses at received levels between 122-138 dB (re 1 Pa), and observed that the response depended on the size of the herring. Olson (1971) reports that herring showed a clear behavioural response to 0.1 kHz signals when the signal was 20-25 dB above the ambient noise level.…”
Section: Page 9 Of 24 Mermentioning
confidence: 98%